Crime Reporting on the Online Media Lampost.co: An Analysis of the Journalistic Code of Ethics - Istiani, Ade Nur; Nasution, Nadya Amalia; Syafira, Nanda (Persatuan Wartawan Indonesia, 2024)
This research analyzes the implementation of Article 5 of the Journalistic Code of Ethics in reporting crime on the online media Lampost.co. The Journalistic Code of Ethics is a moral guideline that guides journalists in carrying out journalistic duties with high professionalism and ethics. Lampost.co, as part of the Lampung Post General Daily, co-media has a vital role in maintaining the quality of reporting, especially in the context of crime news. This research uses a field research method with a qualitative descriptive approach. Primary data was collected through purposive sampling from five informants: Chief Editor, one Editor, and three Journalists. Secondary data sources come from photo documentation during news production and relevant theoretical references. Data collection techniques include interviews, observation, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusion. The results of the research showed that there were violations in the application of Article 5 of the Journalistic Code of Ethics in two news stories from the 84 crime stories in the November 2023 edition, where there was a mention of the identity of a minor victim of immoral violence and the face of a minor perpetrator of immoral crime was shown. However, both news have been corrected on the Lampost.co website. Lampost.co explained that the violation was caused by a technical error in the editing process due to pressure to broadcast the news immediately. Meanwhile, other crime news in the same edition complies well with Article 5 of the Journalistic Code of Ethics.